Community-based health insurance dropout and its determinants among women in Sidama National Regional State, Southern Ethiopia, 2024: A multilevel analysis - Kare Chawicha Debessa; Keneni Gutema Negeri; Mesay Hailu Dangisso (PLoS ONE, 2025)
Introduction Ensuring accessible and affordable healthcare continues to be a key priority in low- and middle-income countries, including Ethiopia. To enhance healthcare coverage and provide financial protection, especially for vulnerable populations such as women, community-based health insurance (CBHI) schemes have been introduced. Despite these efforts, dropout rates from the program remain a challenge, threatening its long-term sustainability. This study investigated determinants of CBHI dropout among women in Sidama Regional State, Ethiopia. Methods A community-based cross-sectional study was conducted between December 15, 2023, and January 12, 2024, involving 835 women aged 18 years and above in the central zone of Sidama. Participants were selected via a multistage sampling technique. Data were collected through structured, pre-tested face-to-face interviews encompassing demographic, household, and scheme-related factors. Multilevel logistic regression analysis was performed using Stata version 17 to identify factors associated with CBHI dropout. Adjusted Odds Ratios (AOR) with 95% Confidence Intervals (CI) were reported, with statistical significance set at p < 0.05. Findings Among the 845 women sampled, 835 participated in the interviews with a response rate of 98.8%. Of these, 77 women (9%) dropped from the CBHI scheme (AOR = 9; 95% CI: 7.43% −11.38%; p < 0.001). Lower dropout likelihood was significantly associated with increased age (AOR = 0.93; 95% CI: 0.89–0.97; p < 0.001) and larger family size (AOR = 0.28; 95% CI: 0.17–0.50; p < 0.001). Conversely, reduced transparency in decision-making (AOR = 2.05; 95% CI: 1.39–3.00; p < 0.001) and insufficient advocacy (AOR = 3.01; 95% CI: 2.29–7.00; p = 0.011) were positively associated with dropout. At the community level, residing in low-poverty areas (AOR = 0.29; 95% CI: 0.09–0.98; p = 0.046) and high-autonomy communities (AOR = 0.14; 95% CI: 0.04–0.50; p = 0.002) were associated with reduced dropout rates. Conclusion This study identified factors linked with women’s dropout from the CBHI program that threaten sustainability. Lower dropout rates were linked with older age and larger family size, while poor transparency in decision-making and weak advocacy were associated with increased dropout rates. Communities residing in low-poverty and high-autonomy areas were also associated with decreased dropouts.